Effects of Infrared cooking techniques and Balangu (Lallemantia royleana) gum concentration on quality characteristics and stress relaxation of chicken nugget - Delasa Rahimi; Mahdieh Hasani; Mahdi Kashaninejad (Journal of Food and Bioprocess Engineering, 2020)
In the present study, the effect of Balangu gum (0, 0.25, and 0.5%) and cooking techniques (deep frying, Infrared cooking, Infrared cooking - post frying (IR-PF) and pre frying - Infrared cooking (PF-IR) on the moisture, fat content, color, weight loss, textural characteristics and stress relaxation of chicken nuggets were evaluated. Generalized Maxwell and empirical Peleg models were used to predict the stress relaxation of the nuggets. The interaction of gum concentrations in batter formulation and cooking method showed significant effect only on springiness, cohesiveness and resilience. Three elements Maxwell exponential model demonstrated a better fit to the data with higher adjusted R2 and lower RMSE values than empirical Peleg model. So that, higher and lower elasticity and stiffness were observed in the nugget samples cooked by PF-IR and frying methods, respectively and an increase in Balangu gum concentration remarkably decreased the elasticity and stiffness of samples. Results indicated that the application of IR cooking and Balangu gum in batter formulation might result in a product with desirable texture and color and lower fat content introduced to the food industry as an efficient treatment process.